Membangun citra akademik: Kerangka kerja SMART sebagai model yang efektif untuk komunikasi strategis - Utami, Nabilla Tri Rahayu (Jurnal Mahasiswa Komunikasi Cantrik, 2026)
Increasing competition among universities calls for structured, measurable communication strategies, particularly for building a strong academic identity. Although the literature on university branding continues to grow, research on the implementation of strategic frameworks within Marcomm units at private universities in Indonesia remains limited. This study analyzes the communication strategies of the Marketing Communication (Marcomm) team at the Faculty of Psychology and Social and Cultural Sciences (FPSB) of the Islamic University of Indonesia (UII) in building the institution’s academic image. The study employs a case study approach. Data were collected through in-depth interviews with FPSB Marcomm managers and analyzed using the SMART framework (Specific, Measurable, Achievable, Relevant, Time-bound). The findings indicate that FPSB’s Marcomm strategies specifically target high school students, use digital metrics as indicators of success, align programs with available resource capacity, and design activities based on the academic calendar. This study concludes that the SMART framework is an effective model for guiding strategic communication in higher education institutions with limited resources.